AN ANALYSIS ON STUDENTS’ ERRORS OF ENGLISH PRONUNCIATION FOR SILENT LETTERS - Syaiful, Muhammad; Sakkir, Geminastiti; Sunra, La (Universitas Negeri Makassar, 2024)
Based on the result of the analysis, the researcher concludes that the students made errors in the pronunciation of the words containing silent letters. After analyzing all the data obtained, the researcher found word types of error made by students in Culinary 2 of SMKN 6 MAKASSAR in pre-systematic errors and systematic errors. The dominant type of student pronunciation error is a pre-systematic error. when the researcher analyzed the students' errors directly, the fact is that they did not realize their errors at all. Moreover, the students were not fully aware of evaluating and correcting their pronunciation. It can be concluded, that in pre-systematic errors, the students were at the stage of random guessing where they were vaguely aware of the rules. The students were unaware of some rules because they had no guidance about words in silent letters. Students themselves cannot explain how the error occurred. They could not correct it in silent letters even though the researcher pointed it out. Besides, in the systematic error, the students are familiar with silent letter words but they do not know when or how to apply them in a sentence. The students do not know the silent letter rule in pronunciation, and how to pronounce the words in the silent letters.